# math

-12x^6+24x^5-18x^2/-6x^2=
-4x^8+4x^7-3x

tell me if this right

1. 👍 0
2. 👎 0
3. 👁 60
1. Why have not none check this for me. Let me know if is right. Help me if is wrong.

1. 👍 0
2. 👎 0
posted by Keaton

1. 👍 0
2. 👎 0
posted by JeJ

## Similar Questions

1. ### algebra

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x could some one check this for me please

asked by Ashley on June 4, 2010
2. ### Algebra (Re.: Reiny)

The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 +

asked by Sara on July 20, 2007
3. ### Algebra

checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4

asked by John on October 22, 2007
4. ### algebra

-12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.

asked by Alice v on June 4, 2010
5. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please

asked by Keaton on June 3, 2010
6. ### Math

(2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21

asked by Anonymous on December 13, 2014
7. ### algebra

Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/12x^3-18x^2 - x+1/16x^2-24x = 3.) 2x/x^2-2x-15 - x-2/3x^2+9x =

asked by Sella on August 27, 2012
8. ### math

sums and differences of a rational algebraic expression 3/a + 2/ab + 1/abc another is 2x-1/6 + x+3/12 another is 2/a-b + 3/a+b another is 2a+b/a+b - 2a-b/a-b - 3a^2-b^2/a^2-b^2 another is 2x/2x^2+5x-3 + 5/x^2-9 another is

asked by jazmin on October 8, 2010
9. ### Algebra 1

Rewrite the polynomial in descending order in its simplest form. here is #1 12x^2 y^2 z^3+2+24x^2 I think it should be writen 12x^2y^2Z^3+24x^2+2 then there is also question #6 I need help with is it x+y+xy+3x+4x^2 I think it

asked by Nora on May 28, 2008
10. ### BobPursley..here it is:

Problem 1: (x-2)/(3x+4) - 6x/(x+1) What I did: Common denominator is: (3x+4)(x+1) (x-2)(x+1)/(3x+4)(x+1) - 6x(3x+4)/(x+1)(3x+4) [(x-2)(x+1) - 6x(3x+4)] / (x+1)(3x+4) (x^2 - x - 2 - 18x^2 - 24x) / (x+1)(3x+4) x^2 - 18x^2 = -17x^2

asked by Margie on March 4, 2007

More Similar Questions